Silence as Poetry: Avraham Ben-Yitzhak - Shiffman, Smadar (1999)
This paper attempts to account for Avraham Ben-Yitzhak's poetic silence in terms of the complex relationships between his poetics, his personality, and his literary-historical position as a modernist European poet in Vienna and in Jerusalem of the thirties., Ben-Yitzhak's poetic silence, which began in Vienna and went on unbroken in Jerusalem, has elicited multiple explanations. The paper shows that the personal behavior is in fact another aspect of the same poetic attitude which drove him to opt for minimalist and restrained poetics., The close reading of two of Ben-Yitzhak's poems is used here to demonstrate the consistency of his poetic and personal choices, and the fact that his poetic silence is the almost inevitable consequence of his poetics., The third and last context in which Ben-Yitzhak's silence is dealt with in this paper is his poetic and historical status vis-à-vis Bialik's poetry. In terms of H. Bloom's "Anxiety of Influence," the paper explains Ben-Yitzhak's silence as the ultimate assimilation of the poetic "father" and his poetics into the "son" and his poetry. Ben-Yitzhak's silence is, in fact, a Bialik-like behavior which surpasses Bialik himself.